2017
DOI: 10.1016/j.bonr.2017.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic insight into the effects of Aryl Hydrocarbon Receptor activation on osteogenic differentiation

Abstract: While inhibition of bone healing and increased rates of pseudarthrosis are known adverse outcomes associated with cigarette smoking, the underlying mechanisms by which this occurs are not well understood. Recent work has implicated the Aryl Hydrocarbon Receptor (Ahr) as one mediator of the anti-osteogenic effects of cigarette smoke (CS), which contains numerous toxic ligands for the Ahr. 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD, dioxin) is a high-affinity Ahr ligand frequently used to evaluate Ahr pathway act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…[ 44 ] Also, one of the mediators of the anti-osteogenic effects of cigarette smoking, the aryl hydrocarbon receptor, can adversely affect bone regeneration and bone healing. [ 45 ] Thus, the benefit of tea consumption is likely to be offset significantly by these bad habits in male. This could, however, explain why tea consumption can significantly reduce the risk of OP in female population but not in males.…”
Section: Discussionmentioning
confidence: 99%
“…[ 44 ] Also, one of the mediators of the anti-osteogenic effects of cigarette smoking, the aryl hydrocarbon receptor, can adversely affect bone regeneration and bone healing. [ 45 ] Thus, the benefit of tea consumption is likely to be offset significantly by these bad habits in male. This could, however, explain why tea consumption can significantly reduce the risk of OP in female population but not in males.…”
Section: Discussionmentioning
confidence: 99%
“…Since the effects of dioxin on bone formation are likely mediated at least in part by the AhR [ 12 ], we hypothesized that co-treatment with dioxin and the AhR antagonists ANF, resveratrol, or DIM could prevent the dioxin-mediated inhibition of osteogenic differentiation. In preliminary work, we showed that at the relevant time points, cell proliferation was not inhibited by 0.5 µM ANF, 4 µM Res, and 10 μM DIM, and we subsequently used these doses for co-treatment studies.…”
Section: Resultsmentioning
confidence: 99%
“…While it has been posited that a number of constituents of cigarette smoke—including nicotine—may play a role in the smoking-mediated inhibition of bone healing, the role of the aryl hydrocarbon receptor (AhR) has become a recent focus of active research [ 35 , 36 ]. The AhR is responsible for regulating xenobiotic metabolism and mediating the toxicity of environmental planar aromatic hydrocarbons, with previous studies suggesting deleterious effects of AhR hyper-activation on bone biology [ 12 , 13 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations